PENGARUH PIK-R ( PUSAT INFORMASI DAN KONSELING REMAJA) TERHADAP PERILAKU SISWA (ANGGOTA PIK-R) DALAM MENGKOMUNIKASIKAN PROGRAM GENRE ( GENERASI BERENCANA) (Studi Kasus : SMA N 5 Kota Bengkulu) - Yori Manis Tika (Fakultas Pertanian, 2022)
This study entitled Effect of PIK-R (Center for Information and Counseling Adolescents) on student behavior (member PIK-R) in communicating program genre (Generation Planning) at SMA N 5 Bengkulu City. The purpose of this study was to determine the effect of PIK-R (Center for Information and Counseling Adolescents) on student behavior (member PIK-R) in communicating program genre (Generation Plan). This study uses the theory of group communication. The variables in the study was PIK-R (Center for Information and Counseling Adolescents) as a variable X and the behavior of the students as a variable Y. This research was conducted in August 2015 by using the techniques of data collection questionnaire and literature study, to suspensions and measurement criteria based on the Likert scale scores 1-5. The sample in this research is the whole activity PIK-R in SMA N 5 Bengkulu city, the technique determination of sample that is in the census, respondents numbered 50 people and research methods are quantitative analyzed using simple linear regression analysis and assisted by SPSS version 17. This study used some components as a guide to answer the questions in the desired, these components include the PIK-R (X) and student behavior (Y). From result of respondents giving the results of the genre in the delivery of program material PIK-R activities significantly influence the behavior of students on the knowledge, attitudes and actions. Based on calculations of regression using SPSS version 17, the obtained results were significant influence Value Event PIK-R (X) of the student's behavior (Y) of 0001 <alpha 0.05, which has the meaning that the activity PIK-R (X) effect significantly influence student behavior (Y). With the results of the hypothesis if the hypothesis significance value less than 0.05, then Ho is rejected and Ha accepted, and that means the H test results received because the significance value less than 0.05.